(untitled) (Materiali di Estetica. Terza serie, 2022)
This essay discusses some traits of the research path of Egle Becchi starting from the essential questions and heuristic constructs that have characterised it over the years, not least the development of a reflection on the concept of connoisseurship as a perspective for the analysis of pedagogical phenomena. Re-reading some aspects of this path where the theme of taste, the ability to choose and discriminate, the aesthetic quality of proposals and research in pedagogy, together with a specific process of acculturation, plays here a central role, the essay also discusses subjects, figures and places of education from a contextual and diachronic perspective, in both theory and practice